STUDENTSâ€™ STRATEGIES AND PROBLEMS IN TRANSLATING A POEM - Maharani Pratiwi; Tanto Setia Mulyanto; Anne Ratna Suminar (English Education and Applied Linguistics Journal (EEAL Journal), 2019)
This study, entitled â€œStudentsâ€™ Strategies and Problems in Translating a Poemâ€ was conducted at the English program in one college in Garut area, West Java, involving six students of the sixth semester. It aimed to analyze the strategies they applied and the problems they encountered in translating an English poem entitled A Dream Within a Dream by Edgar Allan Poe into Indonesian. Using the qualitative case design, the data was collected from the documents of studentsâ€™ translation works and interview and was analyzed through textual descriptive analysis. The data was analyzed using Lefevereâ€™s (1992) theory of seven poetry translation strategies and Hariyantoâ€™s (2003) theory about poetry translation problems. The findings of the study revealed that Literal Translation (38%) was the most used strategy, followed by Interpretation (24.7%), Metrical Translation (20%), Poetry into Prose (12%), and Rhymed Translation (5.3%). However, two other strategies, namely Phonemic Translation and Blank Verse Translation, were not found to be used at all by the students. This study also found that the main problem they encountered was Linguistic Problems, more specifically vocabulary, while the second main problem was Literary or Aesthetic Problems, more specifically the rhymes of the poem. It is recommended that further research to be conducted in a different setting and using a different kind of poem to give more information regarding studentsâ€™ strategies and problems in translating a poem.